Fraud and bank performance in Nigeria: VAR granger causality analysis - Adewale Muritala Taiwo; Muftau A. Ijaiya; Olatanwa H. Afolabi; Abdulrasheed B. Yinus (Financial Internet Quarterly, 2020)
This paper examines the causality between fraud and bank performance in Nigeria over the period 2000-2016 for quarterly financial data using Johansen's Multivariate Cointegration Model and Vector Autoregressive (VAR) Granger Causality analysis. The results show a long-run relationship between the variables. Bank performance was found to be linked to Granger fraud variables and vice versa at 10% significant level. This study reveals that there was a direct causal relationship between bank performance and fraud because increase in fraudulent activities in the banking sector leads to reduction in bank performance. Hence, this study recommends that internal control systems of banks should be strengthened so as to detect and prevent fraud. In this way, bank assets would be protected.
Keywords: C01; G21; G30; G34; O55; 330; Granger Causality; Fraud; Bank Performance; NDIC; Nigeria